Summative and formative style anatomy practical examinations: do they have impact on students' performance and drive for learning? - Mogali, Sreenivasulu Reddy (2022)
Anatomical knowledge is commonly assessed by practical examinations that are often administered in summative format. The format of anatomy practical examination was changed at the Lee Kong Chian School of Medicine in Singapore from summative (graded; must pass) to formative (ungraded; no pass/fail) in academic year (AY) 2017-2018. Both assessment formats were undertaken online, but the formative mode used a team-based learning activity comprising individual and team assessments. This gave an unique opportunity to investigate: (1) the impact of two different online assessment formats on student performance in practical examination; (2) the impact of new formative practical examination on students' performance in summative examinations; and (3) students' opinions of these two practical examination formats. The class of 2021 perceptions was obtained as they experienced both formats. A retrospective cohort study was also conducted to analyze the Year 2 students' performance in anatomy practical and year-end summative examinations of cohorts AY 2015-2016, AY 2016-2017 (summative format), and AY 2017-2018 (formative format). There were no significant differences in students' performance between two practical examination formats. The cohort who experienced the formative format, performed significantly better in summative examinations (mean ± SD: 82.32 ± 10.22%) compared with the cohort who experienced the summative format (73.77 ± 11.09%) (P < 0.001). Students highlighted positive features of the formative practical examination, including team reinforcement of learning, instant feedback, and enhanced learning. These findings indicate that students continue to study for anatomy practical examination without the need for external drivers. The team-based learning style practical examination enhances students' performance in summative examinations.